2019
DOI: 10.1891/1541-6577.33.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Associations Among Older Adults' Characteristics and Planned Nursing Interventions Using Electronic Health Record Data

Abstract: Background and Purpose: Little is known about how nursing assessments of strengths and signs/symptoms inform intervention planning in assisted living communities. The purpose of this study was to discover associations among older adults’ characteristics and their planned nursing interventions. Methods: This study employed a data-driven method, latent class analysis, using existing electronic health record data from a senior living community in the Midwest. A convenience sample comprised de-identified data of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…This descriptive comparative study of standardized consumer-generated health data examined strengths, challenges, and needs for women with and without Circulation signs/symptoms. Our findings align with previous research using the Omaha System to document whole-person health, including strengths, demonstrating equivalent resilience for women with and without Circulation signs/symptoms 27,33,36,52 . Challenges and needs differed by domain and group.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This descriptive comparative study of standardized consumer-generated health data examined strengths, challenges, and needs for women with and without Circulation signs/symptoms. Our findings align with previous research using the Omaha System to document whole-person health, including strengths, demonstrating equivalent resilience for women with and without Circulation signs/symptoms 27,33,36,52 . Challenges and needs differed by domain and group.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings align with previous research using the Omaha System to document whole-person health, including strengths, demonstrating equivalent resilience for women with and without Circulation signs/symptoms. 27,33,36,52 Challenges and needs differed by domain and group. The Simplified Omaha System Terms embedded in a web-based mobile enhanced application enabled reuse of structured strengths-based consumer-generated health data for knowledge discovery.…”
Section: Discussionmentioning
confidence: 99%
“…The University of Minnesota Center for Nursing Informatics Omaha System Partnership and Nursing Knowledge Big Data Science initiatives are leading efforts to advance the use of standardized data across settings and systems to advance knowledge discovery to improve population health (Delaney & Weaver, 2019; Pruinelli et al, 2016). Numerous previous studies have demonstrated the value of data generated by structured documentation for use in clinical trials and big data science initiatives using visualization techniques and machine learning methods for pattern discovery, hypothesis generation, and testing (e.g., Bose, Maganti, Bowles, Brueshoff, & Monsen, 2019; Gao et al, 2019; Kaya, Secginli, & Olsen, 2020; Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…6,7,[18][19][20] A whole-person assessment is supported by the Omaha System, a multi-disciplinary standardized terminology used for EHR documentation by nurses and other clinicians, which both aggregates and makes interoperable health assessments for reuse in clinical settings and research. 9,21,22 Toward better consumer-generated whole-person health data, the Omaha System was simplified to the fifth-grade reading level and embedded within the MyStrengths+MyHealth (MSMH) application. 9,23,24 In adapting a whole-person assessment for populations with health literacy challenges, we compare the language of data capture and reuse of usual health assessments and those of MSMH (Figure 1).…”
mentioning
confidence: 99%
“… 4 Using a whole-person health approach, it becomes possible to capture, organize, and report data that include strengths (discrete aspects of resilience), challenges (signs/symptoms), and needs (interventions to address challenges) across four domains of health including SBDH 6,7,18–20 . A whole-person assessment is supported by the Omaha System, a multi-disciplinary standardized terminology used for EHR documentation by nurses and other clinicians, which both aggregates and makes interoperable health assessments for reuse in clinical settings and research 9,21,22 . Toward better consumer-generated whole-person health data, the Omaha System was simplified to the fifth-grade reading level and embedded within the MyStrengths+MyHealth (MSMH) application 9,23,24 .…”
mentioning
confidence: 99%